Recollection from a great antiquity: a feasibility study of jewelry with near-filed communication (NFC) - Abanto, Miggle Antonio D., Cunanan, Kristine Gem S., De Ramos, Carleen Althea J., Ghalaini, Abdullah A., Laus, Rhaizelle G., Marte, Edison Smith C., Montano, Patricia Anne Marie C., Oriel, Jamela Nicole L., Sharief, Cyana I., Tanilog, Gabrielle A. 4 0 16; 5
ABSTRACT: The study examines the feasibility and viability of venturing into the fashion jewelry industry by establishing a small-scale online business within the Philippine capital region. The said products, which will initially start with necklaces and pendants, will be combined with another essential component - a Near-Field Communication Chip or NFC Chip, which will provide numerous technological features for the offered jewelry. Using said NFC-integrated products, storing and viewing online data could be possible by simply pairing the jewelry with an NFC-enabled smartphone. Historically speaking, pieces of jewelry are an integral part of Philippine culture or history which could even be traced back to the pre-colonial era when these products were mostly linked to religious ceremonies or rituals, supernatural beliefs, or sometimes used as a symbol of one's status in society. Moreover, these fancy trinkets are used for numerous aspects applicable to today's generation; their versatility and potential to create a community can be relevant and significant, mainly in fashion, art appreciation, and even culture. On the other hand, NFC technology identity in society is distinguished through devices, commonly smartphones. It has features and beneficial facets that nurture the ideologies of developing a helping hand toward the economy. Memoir el Colgante, set forth a business that endeavors the possibilities of technology in changing how individuals foresee its drawbacks and hindrances to the general public. Therefore, the company strives to influence consumers to express their standards in creating a product that acknowledges the importance of its core purpose. Lastly, Memoir el Colgante differentiates and correlates jewelry in its customers' daily lives, leaving it with inclusions that the product user would never neglect.
Feasibility Study: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2